STUDENTS’ VOCABULARY AND READING COMPREHENSION: IS IT CORRELATED? - Adriana Bombo; I Gde Putu Agus Pramerta; Dewa Gede Agung Gana Kumara (Academic Journal on English Studies (AJOES), 2022)
This study aimed at finding out the correlation between students’ vocabulary mastery and reading comprehension. The study made use of a correlational research design. The sample was 63 eighth-grade students of SMP Wisata Sanur in the academic year 2021/2022. A random sampling technique was used by having paper rolls. The multiple-choice test was used as the instrument for collecting the data. The data were analyzed by using SPSS 25, which consisted of a normality test, homogeneity test, hypothesis testing, and T-test. The result showed that vocabulary and reading comprehension correlated significantly. When the students had a high vocabulary, their reading comprehension showed good criteria. The result of the normality test for vocabulary was 0.112 and reading comprehension was 0.265; the homogeneity test was 0.085; the hypothesis test was 0.602, andthe t-test was 0.000. It means that there was a significant correlation between students’ vocabulary mastery and reading comprehension. Further study is recommended to be conducted to have deeper data.